Metacognition in Japanese macaques (Macaca fuscata): does impulsivity explain unnecessary looks in the tubes task? - Lorraine Subias; Noriko Katsu; Kazunori Yamada (Animal Cognition)
Abstract Potential metacognitive abilities, such as monitoring and controlling cognitive processes, have been revealed in some primate species. In the tubes task, apes and macaques showed higher content-checking behavior when unaware of a reward’s location, but they also periodically inspected the tubes when aware, especially when a more appealing reward was involved. Some attribute this to the pleasure of looking at the reward. This study investigates whether the unnecessary tube-checking behavior observed in nine wild Japanese macaques, previously tested for metacognition using the tubes task, can be solely attributed to impulsivity. The macaques’ propensity to look inside a single tube containing food they cannot immediately reach was measured and compared to their behavior in the tubes task. Results indicated that looking inside the baited tube increased as reward quality improved. However, macaques displaying unnecessary tube inspections in metacognitive tests showed less impulsivity to look. This intriguing result counters the notion that excessive looking in the tubes task is solely due to impulsive looking, prompting us to advocate for further research into the relationship between inhibition and metacognitive performance.